PENGARUH DAN STATUS EKONOMI KELUARGA TERHADAP PENDIDIKAN ANAK DI MASA PANDEMI COVID-19 - Nur Afni (Scolae: Journal of Pedagogy, 2020)
Education is not only useful for individuals in order to improve knowledge, but also as a business community for society in general and the family economy in particular. Education is a path to progress to achieve social welfare and create a stable country's economy, while failure to build education will give birth to various kinds of problems. We can reflect on developed countries which prioritize education to support quality human resources. Considering that in entering the world of work, the next generation of the nation is faced with increasingly large challenges so that it must be balanced with skills and qualified education. The more qualified the next generation of a country, the higher the rate of economic growth and can create a prosperous society. The economic influence on children's education is very large, education is expected to support the process of economic life and can even influence the direction of the economic development process because the actors of economic life are humans themselves. Furthermore, economic development in turn will support the realization of the educational process needed in economic development (Kabar Pendidikan.id/2021). Loss of parental income or loss of household income that occurs suddenly causes instability in the family's economic situation and can lead to poverty. The atmosphere of the Covid-19 pandemic has brought back awareness of the importance of family education which has been rarely done or even neglected by some families. During the Covid-19 pandemic, the family economy is disrupted, while children's education must continue, children still have to learn from home which requires cellphones, laptops, credit, quota, internet and so on.